2016
DOI: 10.2217/bmm.15.118
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Plasma Vitamin D and Non-HDL Cholesterol Reflect the Severity of Cerebral Cavernous Malformation Disease

Abstract: Aim: To correlate cerebral cavernous malformations (CCMs) disease aggressiveness with peripheral blood biomarkers hypothesized mechanistically. Patients & methods: A prospective case–control study enrolled 43 CCM patients, where 25-(OH) vitamin D, HDL and non-HDL cholesterol, CRP plasma levels and leukocyte ROCK activity were correlated with parameters of disease aggressiveness reflecting chronic and acute domains. Results: Patients with one or more features of chronically aggressive disease (early age at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…Overall, it is plausible that the impaired endothelial function that may accompany low circulating vitamin D levels contributes to an increased risk of cerebrovascular diseases and mortality. Indeed, there is increasing interest in how vitamin D levels might influence the onset and severity of cerebrovascular diseases, including stroke [145][146][147][148][149][150] and cerebrovascular malformations [43,95,117,128,151,152].…”
Section: Vitamin D Deficiency and Its Impact On Cerebrovascular Diseasesmentioning
confidence: 99%
“…Overall, it is plausible that the impaired endothelial function that may accompany low circulating vitamin D levels contributes to an increased risk of cerebrovascular diseases and mortality. Indeed, there is increasing interest in how vitamin D levels might influence the onset and severity of cerebrovascular diseases, including stroke [145][146][147][148][149][150] and cerebrovascular malformations [43,95,117,128,151,152].…”
Section: Vitamin D Deficiency and Its Impact On Cerebrovascular Diseasesmentioning
confidence: 99%
“…Correlation of clinical aggressiveness with biomarkers, determined either biologically or by using neuroimaging techniques, has also being progressively subjected to several studies [30,31,32] in order to better understand the distinct clinical behavior of the patients harboring CCMs. Main limitations of this study are the retrospective nature, small sample, and the fact that it was being originated from a reference center; these factors might not represent adequately the non-intervention CCM population.…”
Section: Resultsmentioning
confidence: 99%
“…In an in vitro study by Gibson et al [2], vitamin D3 was found to restore structural abnormalities in human endothelial cells deficient in CCM2. In a clinical study by Girard et al [3], 43 CM patients underwent labora- tory testing to assess 25-hydroxy-vitamin D, approximately half of whom were familial form. Patients were stratified into "acute" and "chronic" aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, vitamin D has been shown to play a role in CM endothelial leakiness in animal and in vitro models [2]. Only one study has assessed the influence of 25-hydroxy-vitamin D level on the clinical course of patients with CM [3]. In that study, lower 25-hydroxy-vitamin D was found in CM patients with "chronically aggressive disease" defined as one of the following: early age at symptom onset, 2 or more symptomatic hemorrhages, or high lesion burden.…”
Section: Introductionmentioning
confidence: 99%